Genitourinary melioidosis: a descriptive study. (April 2019) - Koshy, Maria; Sadanshiv, Prashansa; Sathyendra, Sowmya
Melioidosis is the disease caused by the soil and water bacterium, Burkholderia pseudomallei . Our study aimed to delineate its genitourinary manifestations. Over a 10-year period (2006–2016), 20 adults with culture-confirmed genitourinary melioidosis were identified. The patients were all men with a mean age of 45.3 ± 12.3 years. The common risk factors were diabetes mellitus (65%) and alcoholism (25%); a majority of patients (90%) had chronic melioidosis. Most had disseminated disease (n = 17) and 55% were bacteraemic. The prostate was the organ most frequently involved (60%, n = 12), followed by the kidney, bladder and seminal vesicles. Diagnosis was established by blood and urine cultures and imaging. Patients were successfully treated with ceftazidime intensive therapy followed by eradicative therapy, with surgical debridement and guided aspiration, when deemed necessary. There was one case fatality and no relapses. Melioidosis is an important differential to be considered in chronic genitourinary infections in the appropriate setting.